Influência da redução do teor de nitrito de sódio na estabilidade oxidativa e avaliação microbiológica de linguiça suína frescal - Figueiró, Lorane Sarmento (2013)
The processing of cured meat products involves some chemical preservatives such as sodium nitrite aiming to preserve, modify sensory traits and diversify production. Addition of nitrite has been associated with a negative image as regards the health of consumers due to the formation of nitrosamine, which has led the food industry to reconsider the amount of nitrite used. Given this scenario, the objective of this study was to evaluate the influence of the sodium nitrite concentration on the oxidation stability and microbiological count of fresh pork sausage. Sausage samples containing 0, 50, 100, 150 and 200 mg.kg-1 sodium nitrite were prepared, vacuum-packed and stored at 5 ºC. We evaluated the lipid oxidation profile, by the number of substances reactive to thiobarbituric acid (TBARS), color, pH, acidity and quantification of residual nitrite throughout the storage period (Days 1, 8 and 15). The microbiological evaluation was performed by counting the total coliforms (NMP.g-1); thermo-tolerant coliforms (NMP.g-1), psychrotrophic microorganisms (Log.cfu.g-1) and coagulase-positive Staphylococcus (cfu.g-1) on days 0, 7 and 14. During the studied period, a TBARS of 0.24 mg.kg-1 was observed when 50 mg.kg-1 nitrite were added, and 0,09 mg.kg-1 when we utilized 200 mg.kg-1, displaying a decrease (P = 0.05) in the number of TBARS as the sodium nitrite concentration was elevated. During the storage time, an increase (P = 0.05) from 0.14 mg.kg-1 to 0.21 mg.kg-1 was observed in TBARS, demonstrating development of the lipid-peroxidation process. With regard to the objective determination of the color, increase was observed (P = 0.05) in the L* values (57.77 to 59.2), whereas the b* values were found to reduce (14.9 to 13.3), and no influence (P > 0.05) of sodium nitrite was observed for any of the color parameters assessed. Although the pH and acidity values had no significant differences at the different concentrations of nitrite, they did show variation (P = 0.05) during the storage period, specifically 5.78 to 5.66 and 7.95 to 9.75% lactic acid, respectively. The residual nitrite contents increased (P = 0.05) from 1.95 to 6.57 mg.kg-1 on the 1st day, when the nitrite concentration rose from 50 to 200 mg.kg-1, but during the conditioning time, it reduced almost completely, presenting levels below 2 mg.kg-1 on the 15th day. In the microbiological evaluation of the fresh pork sausage, counts lower than 1 × 103 NMP.g-1 were observed for total and thermo-tolerant coliforms; for coagulase-positive Staphylococcus all the results were negative, showing it to be in accordance with the Brazilian legislation. At the count of psychrotrophic microorganisms, all treatments presented counts above 6 Log cfu.g-1. Given the aforementioned results, we conclude that all treatments showed to be stable at lipid peroxidation and microbiological evaluation. Thus, it may be possible to reduce the sodium nitrite concentrations used in the preparation of fresh pork sausage. However, before adopting this measure, more studies should be conducted to evaluate the influence of nitrite concentrations on the other variables associated with preservation and safety of fresh pork sausage